Lithuanian Active Labour Market Policy in 2009-2020: a Social Investment Perspective - Daiva Skuciene (Institute of Social Affairs of the Pedagogical University of Cracow, 2021)
An active labour market policy is an integral part of social policy, ensuring support for the unemployed to search for a job through developing their skills. Thus, the active labour market policy is part of the social investment, focusing on investment in people's knowledge. The heart of social investment is the design of policy-enhancing people to work, use their skills, create families and grow up children. The active labour market policy was analysed, focusing on the measures and their development in Lithuania. At the same time, the analysis from the social investment perspective was missing. Thus, this research aims to analyse Lithuania's active labour market policy from the social investment perspective between 2009 and 2020. The choice of the period was determined by the time of the world financial crisis in 2009 and the Covid-19 pandemic crisis in 2020. The analysis of legal documents and Eurostat data for 2009-2018 was used to attain the formulated aim. Additionally, the meta-analysis of the Ministry of Social security and Labour's Social Reports in 2009-2017 was used to analyse active labour market policy development. The research is based on methodology, which suggests classifying the active labour market measures into the strong and weak investments in human capital. A strong investment provides basic education or training, and a weak one creates new jobs, job subsidies, counselling, services for getting the job, job searching programmes, benefits, and taxes allowances. The analysis of the Lithuanian active labour market policy measures revealed that both strong and weak investments in human capital were balanced only during the crises. However, during the inter-crisis period, Lithuania's active labour market policy measures were more focused on the weaker investment in human capital measures or the "job first" strategy. The strong investment in human capital was the lowest in Lithuania among other Baltic countries during the analysed period.  Keywords: active labour market policy, social investment, Lithuania Aktywna polityka rynku pracy na Litwie w latach 2009-2020: perspektywa inwestycji społecznych Aktywna polityka rynku pracy jest ważnym elementem polityki społecznej zapewniającym bezrobotnym wsparcie w poszukiwaniu pracy przez rozwijanie ich umiejętności. Podstawą inwestycji społecznych jest projektowanie polityki zachęcającej ludzi do aktywności zawodowej, zastosowania ich umiejętności, założenia rodziny i wychowania dzieci (Kvist, 2014). W związku z tym badania aktywnej polityki rynku pracy dokonują się na postawie analizy instrumentów i ich rozwoju. Brakuje jednak badań przeprowadzanych z perspektywy inwestycji społecznych. Biorąc pod uwagę powyższe, celem niniejszego badania jest analiza aktywnej polityki rynku pracy na Litwie z perspektywy inwestycji społecznych w latach 2009-2020. Wybór okresu badawczego zdeterminowany był wybuchem światowego kryzysu finansowego w 2009 roku oraz pandemii COVID-19 w roku 2020. Dla realizacji sformułowanego celu zastosowano analizę aktów prawnych i danych Eurostatu za lata 2009-2018. Jako metodę badawczą kształtowania aktywnej polityki rynku pracy wykorzystano ponadto metaanalizę Raportów Społecznych opublikowanych przez Ministerstwo Ubezpieczeń Społecznych i Pracy w latach 2009-2017. Badanie zostało zrealizowane z zastosowaniem metodologii Bonolego (2011), wskazującej klasyfikację mierników aktywnej polityki rynku pracy na podstawie dużych i małych inwestycji w kapitał ludzki. Według Bonolego (2011) wykształcenie podstawowe lub szkolenia zapewniają duże inwestycje w kapitał ludzki, podczas gdy małe są generowane przez tworzenie nowych miejsc pracy, subsydiowanie, doradztwa, pomoc w poszukiwaniu pracy, świadczenia oraz ulgi podatkowe. Analiza litewskich instrumentów aktywnej polityki rynku pracy wykazała, że zarówno duże, jak i małe inwestycje w kapitał ludzki były zrównoważone podczas kryzysów. Mimo to interwencje aktywnej polityki rynku pracy na Litwie w latach 2009-2020 były bardziej skierowane na małe inwestycje w środki kapitału ludzkiego lub realizację zasady "najpierw praca".